IMPROVING STUDENTS’ WRITING ABILITY THROUGH THINK TALK WRITE (TTW) TECHNIQUE BY USING ENGLISH BLOG AS MEDIA - Nofriati, Eli (Jurnal Pendidikan Almuslim, 2016)
The title of this research was improving students’ writing ability through Think Talk Write (TTW) technique by using English Blog as media. the aim of this research were first, to improve the students’ writing ability through Think Talk Write (TTW) technique by using English Blog as media and second, to know the students’ responses toward the implementation of Think Talk Write (TTW) technique by using English Blog as media in learning writing. This research was designed in Classroom Action Research (CAR) and the subject of the research was the fourth semester students which consisted of 30 students. In collecting the data, the researcher used some research instruments such as observation sheets, test, questionnaire and field note. This research was done in two cycles by following the four steps; planning, implementing, observing and reflecting. After all of process of the research was done (cycle 1 and cycle 2), the researcher found some research findings. The first result was found from the observation. It showed that the percentage of the researcher’s performance in implementing the technique by using English Blog as media in teaching writing in cycle 1 was 69% or belongs to level ‘good’ and it increased to be 85% or belongs to level ‘excellent’ in cycle 2. Furthermore, the percentage of the students’ activities in cycle 1 was 63% or belongs to level ‘fair’ and it increased to be 82% or in level ‘good’ in cycle 2. The second result was found from the students’ achievement in writing test. It showed that the average score of the students’ writing test in cycle 1 was 60 or in level ‘fair’ and increased become to 72.33 in cycle 2. The last result was found from the questionnaire and the result showed that the students gave positive response toward the implementation of TTW technique by using English Blog as media in learning writing. It could be proved by the result of questionnaire was 3.48 or belongs to criteria ‘agree’. Based on the research finding above, it can be concluded that the research was done successfully. Key words: Writing, Think Talk Write (TTW) Technique, English Blog